The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21865/ridep55.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Versión Abreviada del Inventario de Perspectiva Temporal de Zimbardo para Buenos Aires

Abstract: Se presenta una versión breve del Inventario de Perspectiva Temporal de Zimbardo (ZTPI) para Buenos Aires que fue construida a partir de la adaptación argentina de 56 ítems y que fue respondida por 343 personas junto con la escala de Malestar Psicológico y la de Autocontrol. A partir de un análisis paralelo clásico y un análisis factorial exploratorio se verificó la estructura original de cinco factores y se llegó a una versión del ZTPI breve (ZTPI-B) de 29 ítems. En un segundo estudio 272 personas completaron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
7
0
4
Order By: Relevance
“…Demographic and academic information: participants completed a questionnaire that collected information, such us age, gender, location, course of degree, year in which they had initiated the career and number of approved signatures. Zimbardo Time Perspective Inventory (ZTPI; Zimbardo and Boyd, 1999): brief local version by Germano and Brenlla (2020) was used to measure the PP time perspective. The ZTPI consists of 29 items distributed among five subscales: past-negative scale (7 items, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic and academic information: participants completed a questionnaire that collected information, such us age, gender, location, course of degree, year in which they had initiated the career and number of approved signatures. Zimbardo Time Perspective Inventory (ZTPI; Zimbardo and Boyd, 1999): brief local version by Germano and Brenlla (2020) was used to measure the PP time perspective. The ZTPI consists of 29 items distributed among five subscales: past-negative scale (7 items, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in future time perspective according to sex have been less consistent than those for age (Kooji et al, 2018). Some studies have reported women to be more future time orientated than men (Brenlla et al, 2016;Germano & Brenlla, 2020;Kooji et al, 2018), and some others have distinguished that men tend to plan further into the future than women (Green & DeBacker, 2004). Furthermore, men's future goals have been said to be more orientated to career-related issues, whilst women have had more and more diverse goals related to work, family, and leisure time (Kooji et al, 2018).…”
Section: Psychological Thoughtmentioning
confidence: 99%
“…Age was segmented considering a previous the mean for age into younger students (aged 18-24; n = 183, 71.2%) and older students (aged 25-44; n = 74, 28.8%).Psychological ThoughtSouth-West University "Neofit Rilski" 2022, Vol. 15(1), 215-241 https://doi.org/10.37708/psyct.v15i1.640Zimbardo Time Perspective Inventory(ZTPI; Zimbardo & Boyd, 1999): brief local version byGermano and Brenlla (2020) was used to measure Future time perspective. The ZTPI consists of 29 items distributed among five subscales: Past-Negative scale (7 items, e.g., I often think of what I should have done differently in my life), Past-Positive (6 items, e.g., I enjoy stories about how things used to be in good old times), Present-Fatalistic (4 items, e.g., Since whatever will be will be, it doesn't really matter what I do), Present-Hedonistic (6 items, e.g., Taking risks keeps my life from becoming boring), and Future (6 items, e.g., Meeting tomorrow's deadlines and doing other necessary work comes before tonight's play).…”
mentioning
confidence: 99%
“…Fue desarrollada por Zimbardo y Boyd (1999) y consta de 56 ítems con cinco opciones de respuesta en una escala tipo Likert, que van desde completamente falso (1) a completamente verdadero (5). Para este estudio se utilizó la adaptación breve del ZTPI para Buenos Aires (Germano & Brenlla, 2020). Este instrumento contiene 29 ítems que evalúan las cinco dimensiones de la PT: Futuro (compuesto por 6 ítems, e.g.…”
Section: Inventario De Perspectiva Temporal De Zimbardo (Ztpi)unclassified